Ayurveda: Between Religion, Spirituality, and Medicine. (28th November 2013) - Kessler, C.; Wischnewsky, M.; Michalsen, A.; Eisenmann, C.; Melzer, J.
Abstract : Ayurveda is playing a growing part in Europe. Questions regarding the role of religion and spirituality within Ayurveda are discussed widely. Yet, there is little data on the influence of religious and spiritual aspects on its European diffusion. Methods . A survey was conducted with a new questionnaire. It was analysed by calculating frequency variables and testing differences in distributions with the χ 2 -Test. Principal Component Analyses with Varimax Rotation were performed. Results . 140 questionnaires were analysed. Researchers found that individual religious and spiritual backgrounds influence attitudes and expectations towards Ayurveda. Statistical relationships were found between religious/spiritual backgrounds and decisions to offer/access Ayurveda. Accessing Ayurveda did not exclude the simultaneous use of modern medicine and CAM. From the majority's perspective Ayurveda is simultaneously a science, medicine, and a spiritual approach. Conclusion . Ayurveda seems to be able to satisfy the individual needs of therapists and patients, despite worldview differences. Ayurvedic concepts are based on anthropologic assumptions including different levels of existence in healing approaches. Thereby, Ayurveda can be seen in accordance with the prerequisites for a Whole Medical System. As a result of this, intimate and individual therapist-patient relationships can emerge. Larger surveys involving bigger participant numbers with fully validated questionnaires are warranted to support these results.